2004
DOI: 10.1136/thx.2004.021915
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory muscle strength and the risk of incident cardiovascular events

Abstract: Background: Maximal inspiratory pressure (MIP) is a measure of inspiratory muscle strength. The prognostic importance of MIP for cardiovascular events among elderly community dwelling individuals is unknown. Diminished forced vital capacity (FVC) is a risk factor for cardiovascular events which remains largely unexplained. Methods: MIP was measured at the baseline examination of the Cardiovascular Health Study. Participants had to be free of prevalent congestive heart failure (CHF), myocardial infarction (MI),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 23 publications
1
54
1
3
Order By: Relevance
“…When compared to respiratory muscle strength with the predicted by the equation of Neder et al [8], there was statistical difference only for MEP data which differ from those of van der Palen et al [18], who found decreased muscle strength in patients with acute myocardial infarction, considering it as an independent risk factor. One possible reason to explain this finding is that in our studied sample we included patients with valve and aortic disease, which may have a positive effect on the values of respiratory muscle strength.…”
Section: Discussionmentioning
confidence: 65%
“…When compared to respiratory muscle strength with the predicted by the equation of Neder et al [8], there was statistical difference only for MEP data which differ from those of van der Palen et al [18], who found decreased muscle strength in patients with acute myocardial infarction, considering it as an independent risk factor. One possible reason to explain this finding is that in our studied sample we included patients with valve and aortic disease, which may have a positive effect on the values of respiratory muscle strength.…”
Section: Discussionmentioning
confidence: 65%
“…Hence, participants who were characterized as "without airflow obstruction" may have included those with a reduced FVC, a consequence of normal aging or restrictive pattern. A reduced FVC has been shown to be a strong predictor of cardiovascular events and mortality (45,46), and may have confounded the association between CT-measured emphysema and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The best value of 3 recordings was used. The FEV 1 and FVC values are expressed as percentages of the predicted values, adjusted for age, gender, and height. The predicted values were those of the European Community of Coal and Steel approved by the European Respiratory Society.…”
Section: Spirometric Functionmentioning
confidence: 99%
“…1 Moreover, hypercapnic respiratory failure caused by inspiratory muscle weakness has been recognized as the leading cause of death among COPD patients. 2 Determining inspiratory muscle strength is therefore useful in evaluating strategies over preventive and therapeutic approaches for improving respiratory muscle strength.…”
Section: Introductionmentioning
confidence: 99%